2001
DOI: 10.1016/s0002-9440(10)64680-9
|View full text |Cite
|
Sign up to set email alerts
|

A Distinctive Pediatric Renal Neoplasm Characterized by Epithelioid Morphology, Basement Membrane Production, Focal HMB45 Immunoreactivity, and t(6;11)(p21.1;q12) Chromosome Translocation

Abstract: We report two cases of a hitherto undescribed pediatric renal neoplasm that is distinctive at the morphological, immunohistochemical, ultrastructural, and cytogenetic levels. On light microscopy, the tumors are composed of nests of polygonal, clear to eosinophilic cells associated with a subpopulation of smaller cells that surround hyaline material. Despite their epithelioid morphology, these tumors do not label immunohistochemically for epithelial markers but instead label focally for melanocytic markers HMB4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
139
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(150 citation statements)
references
References 23 publications
9
139
0
2
Order By: Relevance
“…All the cases had been earlier reported and cytogenetically confirmed. 2,3,5,[12][13][14][15][16][17] Seven cases harbored the translocation t(6;11)(p21;q12), which results in an Alpha-TFEB gene fusion and all showed confirmatory TFEB nuclear immunoreactivity as described earlier. 5 Ten cases had translocations involving Xp11.2, and all ten of these renal cell carcinomas showed confirmatory TFE3 nuclear immunoreactivity as described earlier.…”
Section: Tissue Samplessupporting
confidence: 66%
See 1 more Smart Citation
“…All the cases had been earlier reported and cytogenetically confirmed. 2,3,5,[12][13][14][15][16][17] Seven cases harbored the translocation t(6;11)(p21;q12), which results in an Alpha-TFEB gene fusion and all showed confirmatory TFEB nuclear immunoreactivity as described earlier. 5 Ten cases had translocations involving Xp11.2, and all ten of these renal cell carcinomas showed confirmatory TFE3 nuclear immunoreactivity as described earlier.…”
Section: Tissue Samplessupporting
confidence: 66%
“…1,2 Several distinct gene fusions of TFE3 have been reported, 1,3,4 whereas only the specific t(6;11)(p21;q12) seems to involve the locus of TFEB. 2 These translocations result in the contribution of strong promoters that cause overexpression of the TFE3 fusion proteins or the native TFEB, such that they become detectable by immunohistochemical analysis. 5,6 Both TFE3 and TFEB are closely related members of the MiTF/TFE transcription factor family, which also includes TFEC and MiTF.…”
mentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27][28][29][30][31][32] The putative oncogene, HMGIY (high mobility group protein isoforms I and Y), localized to 6p21 has been proposed to play a role in the development of a number of these neoplasms. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] An identical t(17;17)(q12;p13) was seen in two previous studies. 7,9 Interestingly, an inversion of chromosome 17 [inv(17)(p13q11.2-12)] involving similar breakpoints was observed in case 37 of the present study (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial artificial chromosome (BAC) clones from the immediately flanking genomic regions of TFEB and TFE3 genes were used to generate dual color break-apart Deceptive patterns of TFEB translocation renal cell carcinoma that have been recently recognized include examples with multilocular cystic, [3] oncocytic, [4] eosinophilic papillary, [4] high-grade unclassified, [3,5] chromophobe renal cell carcinomalike, [5] tubulocystic, [6] epithelioid angiomyolipoma-like, [5] or clear cell-like [1,5] features. One example from a series of 8 tumors reported by Argani and colleagues was noted to be extensively sclerotic and ossified, [4] occurring in a 37 year-old man, similar to…”
Section: Fluorescence In Situ Hybridization (Fish)mentioning
confidence: 99%
“…[1] The unique histologic appearance of these tumors was first characterized as including large cells with clear or eosinophilic cytoplasm and a second population of smaller cells with scant cytoplasm arranged around hyaline basement membrane material, resembling rosettes. [1,2] More recently, however, other studies have found that this unique morphology is not always straightforward, and that some molecularly-confirmed TFEB rearrangement tumors may mimic clear cell renal cell carcinoma, chromophobe renal cell carcinoma, tubulocystic renal cell carcinoma, epithelioid angiomyolipoma, multilocular cystic renal cell carcinoma, or high-grade unclassified renal cell carcinoma. [3][4][5][6] One recent series included a single example that was extensively hyalinized and ossified.…”
Section: Introductionmentioning
confidence: 99%